2020
DOI: 10.1093/geront/gnaa131
|View full text |Cite
|
Sign up to set email alerts
|

Caremongering and Assumptions of Need: The Spread of Compassionate Ageism During COVID-19

Abstract: The Coronavirus Disease 2019 (COVID-19) pandemic has highlighted the pervasive ageism that exists in our society. Although instances of negative or hostile ageism have been identified, critical attention to the nuances of ageism throughout the pandemic, such as the prevalence and implications of positive or compassionate ageism, has lagged in comparison. This commentary uses stereotype content theory to extend the conversation regarding COVID-19 and ageism to include compassionate ageism. We offer the ‘caremon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
98
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(105 citation statements)
references
References 20 publications
2
98
0
5
Order By: Relevance
“…These perceptions can increase feelings of pity and, therefore, also helping behaviours ( Cuddy et al, 2007 ). Indeed, there has been an increase in social movements driven by social media to help and support people impacted by the virus ( Vervaecke & Meisner, 2020 ).…”
Section: Benevolent Compassionate Ageismmentioning
confidence: 99%
See 2 more Smart Citations
“…These perceptions can increase feelings of pity and, therefore, also helping behaviours ( Cuddy et al, 2007 ). Indeed, there has been an increase in social movements driven by social media to help and support people impacted by the virus ( Vervaecke & Meisner, 2020 ).…”
Section: Benevolent Compassionate Ageismmentioning
confidence: 99%
“…Social care movements also need to be careful not to reinforce the vulnerability narrative and impressions of older adults as warm but incompetent ( Vervaecke & Meisner, 2020 ). The internalization of these stereotypes could lead future older generations to behave in line with expectations of helplessness ( Levy, 2009 ).…”
Section: Benevolent Compassionate Ageismmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have found that for the population aged 75 years and above, the lockdown can also have consequences on their image, intensifying the occurrence of ageism [11][12][13][14][15] . Furthermore, during the confinement period, older adults were restricted from actively participating in various aspects of everyday life, such as through working and other means of contributing to society, thus highlighting older adults' view as being an inactive segment of society in need of help.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, during the confinement period, older adults were restricted from actively participating in various aspects of everyday life, such as through working and other means of contributing to society, thus highlighting older adults' view as being an inactive segment of society in need of help. In summary, many studies show the risks of ageism on the wellbeing and health of older adults [15][16][17].…”
Section: Introductionmentioning
confidence: 99%